Notes on Aegilops cylindrica (Triticeae, Poaceae) in Iran - Sayed Zabihollah Hosseini; Mohammad Reza Rahiminejad (تاکسونومی و بیوسیستماتیک, 2015)
The present paper deals with the study of the taxonomy of one hundred accessions of Aegilops cylindica collected all around the country, and also Iranian materials and type specimens and related species housed in the Natural History Museum Vienna (W), the Botanic Garden and Botanical Museum Berlin (B), were studied morphologically. The results showed that morphological traits such as length of spike, length of awn, number of spikelet in each spike, presence/absence of hair on spikelets and rachis were highly variable among the studied materials. Based on the results of this study A. cylindica was recognized as having three varieties, all new records, for Iran.